2007
DOI: 10.1063/1.2735592
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of proton conduction in KTaO3 and SrZrO3

Abstract: In the present paper, the authors focus on proton conduction pathways in a cubic perovskite KTaO(3) and an orthorhombic perovskite SrZrO(3). Density functional theory with a generalized gradient approximation is used to find proton binding sites. The nudged elastic band method is used to find transition states between minima. With this potential energy map of binding and transition states, adjacency matrices and their analogs identify four types of conduction paths in KTaO(3). Distortions from these paths are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 25 publications
5
17
0
Order By: Relevance
“…Bilić and Gale 5,6 found pathways for proton conduction in another orthorhombic perovskite, CaZrO 3 , by considering low energy paths and exploring kinetic Monte Carlo pathways. These pathways are consistent with those we have found for orthorhombic systems without a dopant 7,8 and pseudocubic systems with a dopant. 2 Recently, we showed that vertex coding can enumerate all possible simple N-step periodic proton conduction pathways and used it to find pathways for Y / BaZrO 3 .…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…Bilić and Gale 5,6 found pathways for proton conduction in another orthorhombic perovskite, CaZrO 3 , by considering low energy paths and exploring kinetic Monte Carlo pathways. These pathways are consistent with those we have found for orthorhombic systems without a dopant 7,8 and pseudocubic systems with a dopant. 2 Recently, we showed that vertex coding can enumerate all possible simple N-step periodic proton conduction pathways and used it to find pathways for Y / BaZrO 3 .…”
Section: Introductionsupporting
confidence: 91%
“…This is the same shortest optimum pathway found in the undoped system. 8 It is also similar to the lowest energy path in In/ CaZrO 3 path. 6 However, the single C → B rotation in that work maps to two rotations here since four differently oriented binding sites per oxygen are considered.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Since the mechanism suggests a 1 : 1 ratio of protons to trivalent dopant ions, previous proton conduction simulations in perovskites have considered only one proton and one dopant simulations. [4][5][6][7][8][9][10][11][12][13][15][16][17][18][19][20][21][22][23][24][25][26] However, one study 28) on a different perovskite system finds low energy minima in a perovskite with protons only 2.3 Å apart due to lattice relaxation as well as pathways for moving the two protons together. The same study uses a simplified model to show that the two proton motion may in fact be the dominant diffusing defect.…”
Section: Introductionmentioning
confidence: 99%
“…25) In principle, both the excess proton and the probe proton move through the lattice. Since a proton can bind to an oxygen in a perovskite with four possible hydroxyl orientations, [23][24][25][26] after one proton is added to the system, there are only N − 4 possible sites for the second proton where N is the total number of binding sites. As a result, there are N (N − 4) / 2 combinations of two protonated sites when two protons are in the system.…”
Section: Introductionmentioning
confidence: 99%